2014
DOI: 10.4028/www.scientific.net/amr.1079-1080.58
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Extended High-Performance Green Paving Materials

Abstract: Currently, there is a strong need of high-performance and environment-friendly paving materials in Russian Federation. Sulfur dumps near the oil industry enterprises consumes area which otherwise could be occupied by vegetation, contributing to the improvement of the environmental situation. Incorporation of sulfur in bulk building materials contributes to decrease of load to the environment. The results of numerous studies of sulfur-extended asphalt concretes are summarized in the present work. For the suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In particular, in References [ 88 , 110 , 117 ], it was found that the modification of the sulfur composite with dicyclopentadiene leads to a sharp increase in chemical resistance in salt (0.90–0.98), acid (0.78–0.90) and organic (0.95–0.98) environments. Papers [ 89 , 110 , 117 , 126 , 127 ] proposed to modify the surface of the filler particles with a dressing additive (kerosene solutions of liquid rubbers). The resistance of sulfur-based concrete to various chemical environments and biological agents is given in Table 7 , the compositions of which are presented earlier, in Table 6 .…”
Section: Sulfur In the Concrete Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in References [ 88 , 110 , 117 ], it was found that the modification of the sulfur composite with dicyclopentadiene leads to a sharp increase in chemical resistance in salt (0.90–0.98), acid (0.78–0.90) and organic (0.95–0.98) environments. Papers [ 89 , 110 , 117 , 126 , 127 ] proposed to modify the surface of the filler particles with a dressing additive (kerosene solutions of liquid rubbers). The resistance of sulfur-based concrete to various chemical environments and biological agents is given in Table 7 , the compositions of which are presented earlier, in Table 6 .…”
Section: Sulfur In the Concrete Industrymentioning
confidence: 99%
“…Much research has been done to increase the effectiveness of sulfur in concrete production and it has been proven that this waste has useful value for various applications [ 35 , 127 ]. In 2011, Sabour et al [ 124 ] investigated sewage pipes made of sulfur-based concrete.…”
Section: Future Workmentioning
confidence: 99%
“…(Asphalt concrete with the addition of sulfur (technical or modified) received the name sulfur-extended asphalt concrete- SEA [ 10 ]). After cooling, crystallization of sulfur particles is observed, which increases the strength of sulfur asphalt concrete [ 11 , 12 , 13 , 14 , 15 , 16 ]. According to X-ray phase analysis, the formation of sulfur crystals is completed on the 7th day after the preparation of the material [ 17 ].…”
Section: Introductionmentioning
confidence: 99%